A mixed-method review of work-family research in hospitality contexts. (December 2020) - Zhao, Xinyuan (Roy); Ghiselli, Richard; Wang, Jiale; Law, Rob; Okumus, Fevzi; Ma, Jing
Abstract: Through utilizing a mixed-method approach, this study critically reviews and synthesis work-family research in the hospitality contexts. Academic research on work and family relationships of hospitality employees has developed over the last 20 years, and findings have been inconsistent. The present study provides an up-to-date assessment of work-family research in hospitality occupations. First, a narrative literature review identified research progress and trends in terms of publication outlets, research methods, participants, contexts, theories, and terminology. Second, meta-analytic techniques were used to describe the relationships between work-family conflict and some factors that affect it. Both consistent and conflicting information were identified. Work-family conflict significantly relates to employees' work, family and life attitudes. However, there is no evidence indicating that work-family conflicts vary across demographic groups of employees. Managers in hospitality organizations should notice individually specific work-family episodes of their subordinates and take appropriate actions to provide assistance. This is one of the first studies in tourism and hospitality that offers a synthesis of work-family research in hospitality. It offers specific discussions related to theoretical and practical implications. Suggestions for future research are also provided.